2013
DOI: 10.1039/c3tc30240g
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of organic electrochemiluminescence devices with π-conjugated polymer materials

Abstract: This study focuses on a liquid type light-emitting device with simple structure, an organic electrochemiluminescence (ECL) device. To realize long luminescence, polymer ECL devices using pconjugated polymers, poly(2,5-dioctylphenylene-1,4-ethynylene) (PPE) and poly(3-octylthiophene-2,5diyl) (P3OT), were fabricated. The luminescence properties of each device were investigated. Both polymer ECL devices exhibit luminescence from an excited-state polymer which is formed by redox and annihilation reaction. In parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…In contrast, the emitting layer of traditional ECL cells consists of well-established OLED materials dissolved in organic solvents such as acetonitrile [8], 1,2-dichlorobenzene [8,11], benzonitrile [9], and N, N-dimethylformamide [12]. Several studies on ECL have reported on the use of fluorescent dyes [8,12,14] and phosphorescent dyes [9].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast, the emitting layer of traditional ECL cells consists of well-established OLED materials dissolved in organic solvents such as acetonitrile [8], 1,2-dichlorobenzene [8,11], benzonitrile [9], and N, N-dimethylformamide [12]. Several studies on ECL have reported on the use of fluorescent dyes [8,12,14] and phosphorescent dyes [9].…”
Section: Introductionmentioning
confidence: 93%
“…In the current technology, liquid OLEDs and ECL cells typically have a simple device structure fabricated by sandwiching a selected liquid emitter between two glass substrates with electrodes. The gap between the electrodes was preserved by approximately a few micrometers to several hundred micrometers using spacer materials such as insulating films [11], wires [12], glass beads [13], and glass rods [14]. The use of liquid emitters as the emitting layer is expected to provide flexible and crack-free light-emitting layers under repeated bending.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to obtain the patterned multi-color solid-state emitting layers on a single panel, several fabrication methods have been proposed, including the vacuum deposition of small molecular organic materials through a shadow mask [3] and solution processes such as screen [4], gravure [5], and ink-jet printing [6] for electroluminescent polymers. On the other hand, there has been increasing interest in light-emitting devices based on liquid emitters such as liquid OLEDs [7][8][9][10][11] and electrochemiluminescence (or electrogenerated chemiluminescence) (ECL) cells [12][13][14][15][16][17]. ECL phenomena have been studied since the 1960s [18,19], and the emitting layer of traditional ECL cells typically consists of wellestablished OLED materials dissolved in several organic solvents [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, from the viewpoint of the device design, there are technical challenges associated with multi-color light emission features because conventional liquid OLEDs and ECL cells were designed to have a single liquid emitter sandwiched between two electrode-coated glass substrates. The gap distance between the electrodes for the liquid emitting layer was preserved by approximately a few micrometers to several hundred micrometers using spacer materials [7,[13][14][15][16]. Therefore, the development of patterning methods that are employed for small amount of different liquid emitters on a single device is an important step for developing functional multi-color liquid-based light-emitting applications.…”
Section: Introductionmentioning
confidence: 99%